LEXICAL TRANSFER IN INDONESIAN LANGUAGE ACQUISITION AS THE THIRD LANGUAGE (TRANSFER LEKSIKAL DALAM PEMEROLEHAN BAHASA INDONESIA SEBAGAI BAHASA KETIGA) - Abdul Kholiq; Dian Luthfiyati (Jurnal Gramatika, 2020)
Cross-language influence in third language acquisition (TLA) relates to the influence of the first (L1) and second (L2) language on the third language acquisition (L3). This study focuses on the lexical transfers that occur in the acquisition of the Indonesian language as L3. The lexical transfer consists of (1) lexical transfers non-adapted; (2) lexical transfer adapted; and (3) semantic lexical transfers. The subject of this study were BIPA students. The Source of data in this research is the conversation between the researcher and the subject of research and production of the sentence by picture by research subject. Results of the study are lexical transfer non-adapted occurs in lexical transfers into L1 and L2. lexical transfers adapted are made by reconciling my form in English with basic words in the Indonesian language; -nya form in the Indonesian language with the basic form in L1/L2; me- and di- form in the Indonesian language paired with the basic form in L1/L2; and the use of a phrase consisting of a combination of words in Indonesian and L1/L2. Semantic lexical transfers are made by the Indonesian language as L3 by using their forms that are inconsistent with their meaning and using word choices that are inconsistent with the context. This study can provide benefits to Indonesian language teachers for foreign speakers (BIPA) in determining learning strategies that are following the language history of BIPA students. Besides, this research is also useful for researchers or academics who study multilingualism in determining the role of the first and second language in third language acquisition.